Valuemetrics: The Science of Personal and Professional Ethics - Forrest, Frank G. (Value Inquiry Book Series, 1994)
Valuemetrics is an elaboration of Robert S. Hartman's innovative development in the application of an abstract system to the study of ethical problems. The system used for this purpose is a branch of logic called set theory. Set theory fulfills this role because goodness, the fundamental phenomenon of ethics, is defined axiomatically in terms of sets. The similarity of structure between certain elements of set theory and the various types and degrees of goodness makes mathematical accounting of goodness phenomena possible. In the valuemetrics context, value judgments are considered as an assessment of the goodness of something. Therefore, the mathematical system for the accounting of goodness serves as a tool for objectively making many kinds of value judgments and possible attendant ethical decisions. One of the results of this conception, attributable to Hartman, is the birth of the science of ethics. The first half of the book elucidates the theory, terminology, and mathematical system used in valuemetrics, known as Hartmanean algebra. The second half is devoted to the application of this system to the measurement and development of a person's value vision, and the solution of various problems in ethics using the case study technique. Hartmanean algebra will resolve several types of problems such as the determination of right and wrong, good and bad; determining how to redress and amend instances of wrongs and badness; and how to determine when, if ever, wrongs and badness are justified.